(untitled) (International Journal of Environmental Sciences, 2025)
This cross-sectional study assessed bone and joint health in 13-16 years old adolescents in Visakhapatnam using anthropometric (BMI, WHR, MUAC, SF) and physical fitness (HGS, Flamingo, Tapping) measures. Significant interrelationships were found, revealing gender/age-based variations in body composition and strength. The study emphasizes integrated nutritional and physical activity interventions for optimal adolescent bone health and lifelong well-being. Methodology: This cross-sectional study enrolled 13-16 years old adolescents from Visakhapatnam. Non-invasive Nutrition Focused Physical Examination (NFPE) and Fit India Protocol tests measured BMI, WHR, MUAC, SF, HGS, Flamingo balance and tapping test. Data analysis employed t-tests to determine statistical significance between parameters. Nutritional and physical activity consultations were provided to participants. Results: Statistical analysis showed significant interrelationships (p<0.001) between BMI and other health parameters. While most adolescents were normal weight, girls showed higher rates of overweight/obesity and high WHR, and older boys had lower handgrip strength. MUAC was consistently normal, and most participants demonstrated good balance and coordination. Conclusion: The study highlights significant gender and age-based differences in adolescent body composition and physical fitness, underscoring their impact on bone health. Targeted interventions addressing abdominal adiposity in girls and improving hand grip strength in older boys are crucial. Promoting integrated nutritional and physical activity education within schools is vital for long-term skeletal health in this demographic.